A time to learn, a time to teach - Golombek, Diego Andres (2014)
Six years ago we were invited as editors of a special issue of Mind, Brain, and Education devoted to the role of sleep and circadian rhythms on teaching and learning activities (Golombek & Cardinali, 2008). Several authors showed how mental performance varied significantly throughout the day, correlating with fatigue and alertness scales (Valdez, Reilly, & Waterhouse, 2008).